Phospholipase D, a Novel Therapeutic Target Contributes to the Pathogenesis of Neurodegenerative and Neuroimmune Diseases - Zhang, Weiwei; Zhu, Feiqi; Zhu, Jie; Liu, Kangding (Analytical Cellular Pathology, 2024)
Phospholipase D (PLD) is an enzyme that consists of six isoforms (PLD1–PLD6) and has been discovered in different organisms including bacteria, viruses, plants, and mammals. PLD is involved in regulating a wide range of nerve cells’ physiological processes, such as cytoskeleton modulation, proliferation/growth, vesicle trafficking, morphogenesis, and development. Simultaneously, PLD, which also plays an essential role in the pathogenesis of neurodegenerative and neuroimmune diseases. In this review, family members, characterizations, structure, functions and related signaling pathways, and therapeutic values of PLD was summarized, then five representative diseases including Alzheimer disease (AD), Parkinson’s disease (PD), etc. were selected as examples to tell the involvement of PLD in these neurological diseases. Notably, recent advances in the development of tools for studying PLD therapy envisaged novel therapeutic interventions. Furthermore, the limitations of PLD based therapy were also analyzed and discussed. The content of this review provided a thorough and reasonable basis for further studies to exploit the potential of PLD in the treatment of neurodegenerative and neuroimmune diseases.